2022
DOI: 10.3389/fvets.2022.873194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Phytogenic Feed Additive in Preventing Calves' Diarrhea

Abstract: The aims of the present study were to evaluate the preventive and the therapeutic effect of Stodi® as phytogenic feed additive rich in phenolic substances on the calf diarrhea, during the first 24 days of life. A total of 40 calves were included and randomly divided into Group C (control group) and Group T (treated group) with placebo or treatment administration started from the third day of life (T0). Calves belonged to group C received 2 L of warm water, while the calves assigned to group T received 2L of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Previous studies have suggested that the antimicrobial effect of tannins may be related to their ability to impair microbial adhesions and inhibit hydrolytic enzymes such as proteases, carbohydrolases, and cell envelope transport proteins [62,[66][67][68]. Consistent with our findings, several studies have reported enhanced faecal consistency following tannins supplementation, contributing to the reduction in the duration of diarrhoea, delaying its onset, and serving as a preventive measure in calves [29,33,53,69]. On the contrary, some studies did not register a preventive effect on diarrhoea [54,70]; however, a notable improvement in faecal consistency was recorded [54].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have suggested that the antimicrobial effect of tannins may be related to their ability to impair microbial adhesions and inhibit hydrolytic enzymes such as proteases, carbohydrolases, and cell envelope transport proteins [62,[66][67][68]. Consistent with our findings, several studies have reported enhanced faecal consistency following tannins supplementation, contributing to the reduction in the duration of diarrhoea, delaying its onset, and serving as a preventive measure in calves [29,33,53,69]. On the contrary, some studies did not register a preventive effect on diarrhoea [54,70]; however, a notable improvement in faecal consistency was recorded [54].…”
Section: Discussionsupporting
confidence: 91%